In vitro research of anti-HSV-1 activity in different extracts from Pacific oysters Crassostrea gigas - Olicard, Cecile; Didier, Yohann; Marty, Christel; Bourgougnon, Nathalie; Renault, Tristan (Inter-Research, 2005)
Mortalities related to the detection of Ostreid Herpesvirus 1 (OsHV-1) have been previously reported in France among larvae and spat of the Pacific oyster Crassostrea gigas. Adult oysters appear less sensitive to herpesvirus infections, although OsHV-1 has been detected in adults without signs of disease or mortality. This suggests that the virus is able to persist in its host and that adult oysters may be able to control OsHV-1 infection. Little is known about antiviral substances in invertebrates. The present work concerns the research of antiviral substances in adult oyster C. gigas, where putative antiviral activities were monitored using 3 strategies: (1) in metabolites with variable polarity, (2) in peptidic extracts and (3) in crude haemolymph. In vitro antiviral assays were based on inhibition of Herpes simplex virus type 1 (HSV-1) replication in Vero cell monolayers. All extracts presented no cytotoxicity. Antiviral activity was detected in the fresh filtered haemolymph (EC50:425 mu g ml(-1)) and seasonal variation of the haemolymph antiviral activity was monitored.